The role of nursing in the management of urgent normal premature labor: experience report (Research, Society and Development, 2022)
The pregnancy period is a process that impacts the affective, cognitive and behavioral domains of the pregnant woman and everyone involved in this period. During this process, expectations and idealizations of a birth at the physiologically expected time are created. However, gestational complications can be triggered by several variables, impacting the gestational course, and the pregnant woman may end up experiencing preterm labor or preterm labor (PTP), breaking her expectations, causing psychological impacts on her. and their families, where feelings such as frustration, guilt, discomfort, agitation, confusion, instability and fear are manifested by the possibility of negative outcomes for the fetus. This is a descriptive study of an experience report nature, carried out through the experiences of nursing students during a voluntary extracurricular internship in a public hospital located in the interior of Pará, in the municipality of Mocajuba, under the supervision of a professional nurse. Preterm labor occurs most often spontaneously and is associated with several pathologies. The nurse within this context needs to be on surveillance and maintain communication with other sectors, professionals and health units that have structural preparation for intercurrences, since in short, preterm labor progresses to a cessation due to fetal distress, and even when they occur. naturally the baby is born needing NICU. Therefore, a vigilant and qualified nursing is essential to save the life of the mother-baby binomial.